2014
DOI: 10.1016/j.jtcvs.2014.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous perfusion-induced systemic hyperthermia: Five-day sheep survival studies

Abstract: Objective Since hyperthermia selectively kills lung cancer cells, we developed a venovenous perfusion-induced systemic hyperthermia (vv-PISH) system for advanced lung cancer therapy. Our objective was to test the safety/accuracy of our vv-PISH system in five day sheep survival studies, following Good Laboratory Practice standards. Methods The vv-PISH system, which included a double lumen cannula (DLC, AvalonElite™); a centrifugal pump (Bio-Pump 560®); a heat exchanger (BIOtherm™); and a heater/cooler (modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In both animal (Ballard‐Croft et al, ; Oglesbee, Diehl, Crawford, Kearns, & Krakowka, ; Vertrees et al, ) and human (Ash et al, ; Cremer et al, ; Locker et al, ; Zwischenberger et al, ) models hemodynamic changes are observed during eWBH treatment. These changes are attributable to a rapid decrease in systemic vascular resistance due to vasodilatation, resulting in a compensatory increase in heart rate and cardiac output (Faithfull et al, ; Locker et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both animal (Ballard‐Croft et al, ; Oglesbee, Diehl, Crawford, Kearns, & Krakowka, ; Vertrees et al, ) and human (Ash et al, ; Cremer et al, ; Locker et al, ; Zwischenberger et al, ) models hemodynamic changes are observed during eWBH treatment. These changes are attributable to a rapid decrease in systemic vascular resistance due to vasodilatation, resulting in a compensatory increase in heart rate and cardiac output (Faithfull et al, ; Locker et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In one of two animal studies on eWBH performed by Ballard‐Croft et al, a total of 3.070 ± 683 ml (744 ± 205 ml/hr) fluid resuscitation were reported to maintain stable hemodynamics in five sheep during eWBH (2 hr, 42–42.5°C). The second study reported fluid infusion of 100‐500 mL/hr in seven swine undergoing eWBH (2 hr, 42°C) to maintain stable hemodynamics (Ballard‐Croft et al, ). Both studies did not use corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation